Pemberian Npk Organik Sebagai Larutan Nutrisi Pada Pertumbuhan dan Hasil Tanaman Tomat (LycopersicumesculentumMill.) Dengan sistem HidroponiK - Aceng Sumpena; Nurbaiti '; Fetmi Silvina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The objective of the research was to determine the best dose of NPK organic nutrient solution on growth and yield of tomato plants with hydroponics systems. These experiments were prepared using completely randomized design (CRD) with 4 treatments and 4 replications. The treatment in this study are: D1 = organic NPK with dose of 325 g / plant, D2 = organic NPK with dose of 650 g / plant, D3 = organic NPK with dose of 975 g / plant, D4 = organic NPK with dose of 1300 g / plant. Parameters measured were plant dry weight, number of flowers, number of fruits percentage of fruit formation, harvesting age and weight of fruits per plant. The data obtained were statistically analyzed using analysis of variance, followed by Duncan's test New Multiple Range Test (DNMRT) at the level of 5%. The results showed that treatment doses of 975 g / plant showed the highest results in each parameter were observed. Accompanied by an increase in organic NPK dose response primarily to the increase was not significantly different for all parameters were observed. Keywords :Tomato plant, nutrient solution, organic NPK, hydroponic system.